Resource-Poor Farmers in South India On the Margins or Frontiers of Globalization? - Rimjhim M. Aggarwal (Research Paper No. 2006/97, 2006)
It is often argued that an important reason why globalization may lead to GDP growth but fail to reduce poverty is because the poor are unable to participate in the new market opportunities and are marginalized. In this paper we examine the experience of resource-poor farmers in south India, who participated aggressively in the new market opportunities that opened up with trade reforms. However, these expanded market opportunities failed to improve their welfare. The paper examines why and how this happened. As cotton prices increased sharply following the reforms, a number of poor farmers shifted to cotton cultivation. However, cotton cultivation requires much greater technical expertise, working capital, and marketing network than the traditional crops. Interestingly, as state support declined, the network of private traders rapidly expanded to meet not only the marketing needs of the new crops but also to provide working capital and technical expertise. We show how this expanded, and largely unregulated, operation of private traders in multiple markets also provided them with the opportunity to extract greater surplus from the farmers. Thus, while increased participation in external markets exposed farmers to greater price risks and fraudulent